Does "wearing off" of efficacy occur in galcanezumab‐treated patients at the end of the monthly treatment cycle? Post hoc analyses of four phase III randomized trials. Issue 2 (25th January 2022) - Ailani, Jessica; Kuruppu, Dulanji K.; Rettiganti, Mallikarjuna; Oakes, Tina; Schroeder, Krista; Wietecha, Linda; Port, Martha; Blumenfeld, Andrew M.
Abstract: Objective: The purpose of this study was to propose a definition of "wearing off" at the individual patient‐level and determine the percentage of patients with migraine who experience "wearing off" of efficacy of galcanezumab at the end of a treatment cycle using this predefined threshold. Background: Anecdotal reports suggest that some patients may experience "wearing off" of efficacy during the last week of their calcitonin gene‐related peptide monoclonal antibody treatment cycle. A previous post hoc analysis of galcanezumab demonstrated consistent efficacy at each week throughout all monthly dosing intervals at the population‐level, but "wearing off" has not been assessed at the individual patient‐level. Methods: Post hoc analyses of clinical trial data from four galcanezumab phase III, randomized, placebo‐controlled studies in a total of 2680 patients with high‐frequency episodic migraine (EVOLVE‐1, EVOLVE‐2, and CONQUER studies) or chronic migraine (CM; REGAIN and CONQUER studies) were conducted. "Wearing off" was defined as an increase of greater than or equal to 2 weekly migraine headache days in the last week of the treatment cycle compared to the second week for at least 2 months. The analyses were conducted (1) in all patients and (2) in patients with a clinically meaningful response to treatment. Results: The percentage of patients meeting the threshold of "wearing off" was not statistically significantly different among the placebo, galcanezumab 120 mg, and galcanezumab 240 mg treatment groups, both in the total population and in patients with a clinically meaningful response (all ≤9.0%). Although the frequency of "wearing off" in patients with CM and prior preventive failures was numerically greater in the galcanezumab groups (8/89 or 9.0%) compared to placebo (3/95 or 3.2%), these differences were not statistically significant. Conclusions: Consistent with previous analyses at the population‐level that showed no evidence of decreased efficacy at the end of a treatment cycle, rates of individual patients meeting the threshold of "wearing off" in this analysis were low and similar among placebo, galcanezumab 120 mg, and galcanezumab 240 mg treatment groups.